PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP PENYAJIAN KEMBALI LAPORAN KEUANGAN - Vira Fortuna Widyaningrum; Faisal Faisal (Diponegoro Journal of Accounting, 2015)
This study aims to examine the effect of corporate governance characteristics on the financial restatement. Indicators used to measure corporate governance mechanisms in this study are the size of board, proportion of independent board, size of audit committee, audit committee independence, audit committee’s financial expertise, managerial ownership ,and institutional. While financial restatement are measured using dummy variable which used “1” if the firm restate and “0” if the firm non-restate. This study also tests several control variables namely firm size, leverage, profitability, and industry. Data for this study are obtained from annual report of companies listed on Indonesia Exchange Stock (BEI) in 2009-2013. The sampling method used to draw the sample is purposive sampling. Sample contains from 19 restate companies and 19 non- restate companies. A control group comprising between restating firms and non-restating firmsare matched by firm size and industry. The criteria of restatement companies allowed from GAO’s definition of restatement and exclude restatement that was happened due to application of new PSAK, accounting method changes, merge and acquisition that accordance with PSAK, and stock splits or reverse stock. The hypothesis testing use logistic regression analysis.The results show that the size of board and institutional ownership negatively affects the financial restatement.. While proportion of independent board, size of audit committee, audit committee independence, and managerial ownership did not significantly affect restatement. Overall, it can be concluded that two corporate governance characteristics affect with occurance of restatement.